OPTIMIZATION TO INCREASE ENERGY EFFICIENCY OF A SIROCCO CENTRIFUGAL FAN USING COMPUTATIONAL FLUID DYNAMICS (CFD) - Kothe, L. B.; Petry, A. P.; Vecina, T. D. J.; Luz, J. L. R. (Revista de Engenharia Térmica, 2017)
This paper presents a numerical and experimental study on the aerodynamic performance of Sirocco centrifugal fans seeking an increase in energy efficiency. Numerical simulations are performed by the Finite-Volume Method commercial code ANSYS Fluent. Characteristics such as flow rate at the outlet, consumed power and sound pressure levels emitted by centrifugal fans with the original model of 16 blades and the optimized models of 16 and 14 blades are compared. Numerical calculations are performed by the continuity equation, the Reynolds Averaged Navier- Stokes (RANS) equations and the k-ω SST turbulence model. The quality of the mesh is evaluated for three different mesh densities. Results demonstrate that it was possible to obtain an increase of flow rate up to 22.7%, and reductions in the noise levels without increasing the consumption of the electric motor.